Α higher ratio of serum uric acid to serum creatinine could predict the risk of total and cause specific mortality- insight from a US national survey. (1st March 2021) - Mazidi, Mohsen; Katsiki, Niki; Banach, Maciej
Abstract: Introduction: The link between serum uric acid to serum creatinine ratio (SUA/SCr) and mortality has not been studied yet. Methods: We prospectively evaluated the association between SUA/SCr and risk of total and cause specific [cardiovascular disease (CVD) and cancer] mortality by applying on the National Health and Nutrition Examination Surveys (NHANES, 1999–2010). Vital status through December 31, 2011 was ascertained. Adjusted Cox proportional hazard regression models were performed to determine the links between SUA/SCr and mortality. Results: Overall, 20, 209 individuals were included (mean age = 47.5 years, 48.9% men) and 3523 deaths occurred during the 76.4 months of follow-up. In a fully adjusted model, individuals in the fourth (Q4) and third (Q3) quartile of SUA/SCr had a 44 and 35% greater risk of total mortality [risk ratio (RR): 1.44 (95% confidence interval, 95%CI: 1.05–1.98) and 1.35 (1.10–1.66), respectively], as well as a 69 and 47% higher risk of CVD death [RR: 1.69 (1.09–2.62) and 1.47 (1.14–1.89), respectively] compared with the lowest (Q1) quartile. With regard to SUA/SCr and cancer mortality, a significant association was found only between participants in Q4 and those in Q1 [RR: 1.12 (1.06–1.19)] in the partially adjusted model, whereas this relationship became non-significant after further adjustments [RR: 1.15 (0.96–1.39)]. Conclusions: This is the first time that SUA/SCr has been associated with total and cause specific mortality in a large, representative sample of US adults. Further studies are needed to confirm these findings and establish their clinical implications. Highlights: Associations between serum uric acid to serum creatinine ratio (SUA/SCr) with the risk of different mortalities were evaluated. In an adjusted model, SUA/SCr was positively related to both total and cardiovascular disease mortality. The link between SUA/SCr and cancer mortality was significant only in a partially adjusted model.